Penerapan Model Pembelajaran PBL untuk Meningkatkan Hasil Belajar Siswa Kelas III dalam Mata Pelajaran Matematika di MIS Addini - Ritonga, Wiwit Yusnida; Anggraini, Wahyu; Halidza, Nurul; Fadilla, Afrahul; Lubis, Reza Handika Winata (Medan Resource Center, 2024)
The implementation of the Problem-Based Learning (PBL) model aims to evaluate its effectiveness in enhancing students' mathematics learning outcomes. This study focuses on improving the mathematics performance of third-grade students at MIS Addini. The research method includes data collection through learning assessments, observations, and interviews conducted during the PBL-based learning process. The findings indicate a significant improvement in students' mathematics scores, increasing from an average of 77.31 in cycle I to 93.28 in cycle II. This result demonstrates that the PBL model is an effective instructional approach for enhancing students’ mathematics learning outcomes. Furthermore, the study highlights the importance of active learning strategies in fostering students’ problem-solving skills, critical thinking, and conceptual understanding. By engaging students in real-world problem-solving activities, the PBL model promotes deeper comprehension and retention of mathematical concepts. These findings suggest that PBL can be a valuable method for improving student performance in mathematics education.